The Use of Web-Based Information System in Adolescents - Hery Ernawati; Elsi Dwi Hapsari; Lely Lusmilasari (Universitas Airlangga, 2014)
Introduction: Knowledge about reproductive health is very important for adolescents. They can make informed decision on their reproductive health. One of important media that serve as the source of information on reproductive health in adolescents is website. The objective of this study was to find out the relationship between the use of web-based information and knowledge about reproductive health in adolescents.Method: A Cross Sectional was conducted from February 2013 to April 2014, involving the Tenth and Eleventh Grade students of SMA, SMK, MA in Ponorogo Regency. The study was conducted in schools with computer facilities and internet connection, involving 210 adolescents, who were selected using Simple Random Sampling technique. The data was collected by questionnaire. Data analysis was conducted in univariate, bivariate with using Spearman Rank test, and multivariate ways using logistic regression test.Results: The study showed that mean website access frequency and duration for information about reproductive health by adolescents were 1.36 times a week and 1.65 hours; knowledge about reproductive health was 58,1% in low category; and no relationship was found between the use of web-based information system and knowledge about reproductive health in adolescents, even though there was an increasing trend in the frequency and duration of website visits for information related to reproductive health in adolescents.Discussion: The use of web-based information system does not have a significant relationship with knowledge about reproductive health in adolescents. Further research is necessary to explore the same subject with a different method, which is not selecting the respondents in the first meeting and use a closed questionnaire to select the respondents. This way, the adolescents will feel free and open to the researcher.